Implementasi Nasihat “Tentang Beribadah” Berdasarkan Surat Ibrani 10:19–25 Bagi Remaja Pemuda Gereja Kristen Oikumene Faomasi Cimahi Jawa Barat - Astria Gempita Fau; Matius I Totok Dwikoryanto; Hestyn Natal Istanatun (Veritas Lux Mea (Jurnal Teologi dan Pendidikan Kristen), 2026)
Changes in the dynamics of youth worship in the digital age show a decline in spiritual depth, a weakening of discipline in worship attendance, and a shift in youth interest towards more entertainment-oriented forms of worship. This condition is reinforced by the introduction of digital technology and artificial intelligence, which shape the mindset and spiritual behaviour of young people, preventing their theological understanding from developing optimally. In addition, the lack of biblical-based faith formation makes it difficult for adolescents to internalise the true meaning of worship. The phenomenon of increasing dependence on digital worship and passive involvement of adolescents in church communities emphasises the urgency of this research. This study aims to formulate the implementation of advice on worship based on Hebrews 10:19–25 for the worship training of young people at the Oikumene Faomasi Cimahi Christian Church. The research method used is a qualitative-descriptive approach with exegetical analysis of biblical texts and a contextual study of adolescent development. The results of the study indicate that youth worship needs to be built through a correct theological understanding, strengthening of faith identity, and commitment to the church community. The implementation of the advice in Hebrews 10:19–25 provides a strong doctrinal basis for worship training oriented towards maturity in faith. This study concludes that youth worship development must be holistic, contextual, and responsive to the spiritual needs of the digital generation.AbstrakPerubahan dinamika ibadah remaja pada era digital menunjukkan terjadinya penurunan kedalaman spiritual, melemahnya disiplin kehadiran beribadah, serta bergesernya minat remaja kepada bentuk ibadah yang lebih bersifat hiburan. Kondisi ini diperkuat oleh masuknya teknologi digital dan kecerdasan buatan yang membentuk pola pikir dan perilaku spiritual remaja sehingga pemahaman teologis mereka tidak berkembang secara optimal. Selain itu, kurangnya pembinaan iman yang berbasis biblika membuat remaja mengalami kesulitan menginternalisasi makna ibadah yang sejati. Fenomena meningkatnya ketergantungan pada ibadah digital dan keterlibatan pasif remaja dalam komunitas gereja mempertegas urgensi penelitian ini. Penelitian ini bertujuan merumuskan implementasi nasihat tentang beribadah berdasarkan Ibrani 10:19–25 bagi pembinaan ibadah remaja Gereja Kristen Oikumene Faomasi Cimahi. Metode penelitian yang digunakan adalah pendekatan kualitatif-deskriptif dengan analisis eksegetis teks Alkitab dan kajian kontekstual perkembangan remaja. Hasil penelitian menunjukkan bahwa ibadah remaja perlu dibangun melalui pemahaman teologis yang benar, penguatan identitas iman, dan komitmen terhadap komunitas gereja. Implementasi nasihat Ibrani 10:19–25 memberikan dasar doktrinal yang kuat bagi pembinaan ibadah yang berorientasi pada kedewasaan iman. Penelitian ini menyimpulkan bahwa pembinaan ibadah remaja harus bersifat holistik, kontekstual, dan menjawab kebutuhan spiritual generasi digital.